2013
DOI: 10.1152/ajpregu.00055.2013
|View full text |Cite
|
Sign up to set email alerts
|

Increased ventricular stiffness and decreased cardiac function in Atlantic cod (Gadus morhua) at high temperatures

Abstract: We employed the work loop method to study the ability of ventricular and atrial trabeculae from Atlantic cod to sustain power production during repeated contractions at acclimation temperatures (10°C) and when acutely warmed (20°C). Oxygen tension (Po2) was lowered from 450 to 34% air saturation to augment the thermal stress. Preparations worked under conditions simulating either a large stroke volume (35 contractions/min rate, 8-12% muscle strain) or a high heart rate (70 contractions/min, 2-4% strain), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 59 publications
7
23
1
Order By: Relevance
“…Given that Hill et al () reported a 25% reduction in contractile force by Chinook salmon ventricle strips exposed to 10 mg/L metomidate, and the fact that we had to use an even higher concentration of metomidate to anesthetize white sturgeon (25 mg/L) in the current study, we assessed in supplementary experiments whether exposure to relevant concentrations of metomidate affected the in vitro contractile properties (capacity to produce work) of cardiac tissue in northern pike, rainbow trout and white sturgeon. The approach and apparatus used are as described in Syme, Gamperl, Nash, and Rodnick () and Roberts and Syme (, ). Briefly, fish were killed by a blow to the head followed by pithing; no anesthetic was used during euthanasia to allow assessment of contractile performance both with and without exposure to anesthetics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Hill et al () reported a 25% reduction in contractile force by Chinook salmon ventricle strips exposed to 10 mg/L metomidate, and the fact that we had to use an even higher concentration of metomidate to anesthetize white sturgeon (25 mg/L) in the current study, we assessed in supplementary experiments whether exposure to relevant concentrations of metomidate affected the in vitro contractile properties (capacity to produce work) of cardiac tissue in northern pike, rainbow trout and white sturgeon. The approach and apparatus used are as described in Syme, Gamperl, Nash, and Rodnick () and Roberts and Syme (, ). Briefly, fish were killed by a blow to the head followed by pithing; no anesthetic was used during euthanasia to allow assessment of contractile performance both with and without exposure to anesthetics.…”
Section: Methodsmentioning
confidence: 99%
“…The approach and apparatus used are as described in Syme, Gamperl, Nash, and Rodnick (2013) and Syme (2016, 2018).…”
Section: Effects Of Metomidate On Contractile Performance Of Isolatmentioning
confidence: 99%
“…When the temperature of ventricular trabeculae from Atlantic cod was increased from 10 to 20°C, the amount of work required to lengthen the preparations nearly doubled ( Syme et al, 2013 ). The authors suggest that this was due to an increase in the resting tension of the muscle ( Syme et al, 2013 ).…”
Section: Influence Of Warm Acclimation On the Structure And Function mentioning
confidence: 99%
“…When the temperature of ventricular trabeculae from Atlantic cod was increased from 10 to 20°C, the amount of work required to lengthen the preparations nearly doubled ( Syme et al, 2013 ). The authors suggest that this was due to an increase in the resting tension of the muscle ( Syme et al, 2013 ). Such a response could be caused by the increase in temperature enhancing the Ca 2+ sensitivity of the myofilament, thereby increasing the number of active cross-bridges during diastole ( Gillis et al, 2005 , 2000 , 2003b ; Gillis and Tibbits, 2002 ).…”
Section: Influence Of Warm Acclimation On the Structure And Function mentioning
confidence: 99%
See 1 more Smart Citation